Creating Community Bond through Cultural Branding to Maintain Community-Based Schools - Hidayatun, Hidayatun; Rusdarti, Rusdarti; Haryono, Haryono; Soesilowati, Etty (Universitas Negeri Semarang, 2017)
The increase in people’s prosperity and education level create a change on their view about education and the need for it. Consequently, they choose an education institution in a more selective consideration. Schools under Ma’arif institution in Semarang regency faced some difficulties as the impact. They had negative students growth values in the last three years before the research was conducted. In order to survive, institution's management strategy needed to be evaluated. This research examined the interface between culture and school, with specific reference to branding. The purpose of this research was to develop a cultural branding model for junior high schools under Ma’arif institution. Therefore, it includes research and development (R&D) systematic activities. This study was carried out on a premise that creating a bond between a school and its community by adopting the community’s culture in a formal education setting will help the school to gain certain positioning in their community. After a limited implementation on a Ma’arif’s school, the pilot project school underwent a significant increase in a number of new students. The analysis on the fact resulted in a conclusion that implementation of cultural increase community’s love, emotional attachment, and loyalty to the school. The study also suggested applying the model in a wider scope, at least in regency area as it is only implemented in a school as a pilot project. Applying the model in the different type of schools in wider scope will add the worthy value and benefit of the model.